Perkembangan Teknologi Membantu Penerapan Layanan Bimbingan Konseling Di Sekolah Dasar - Riska Ariyanti Nur Fauzia; Siti Insan Cita; Ghea Syara Adinda; Aisil Azijah; , Rista Amelia; Pevi Esviani; Feida Noorlaila Isti’adah (Jurnal Pendidikan Sosial Dan Konseling, 2025)
The development of technology has a significant impact on various aspects of education, one of which is guidance and counseling services (GC). This study aims to explore how technology can assist in the implementation of GC services in elementary schools (SD), with a focus on the benefits, challenges, and proposed solutions. This research uses a qualitative method with a case study approach. Data were collected through in-depth face-to-face interviews with two elementary school class teachers. The interview guide was developed with open-ended questions, allowing the informants to freely share their experiences. Additionally, this study includes a literature review from books, journals, articles, and other relevant scholarly sources. The interview results were analyzed descriptively and systematically to provide a deep understanding of the observed phenomenon. Technology can help counselors deliver more efficient and engaging GC services through digital media, such as applications and online platforms. Moreover, technology also strengthens collaboration between teachers, parents, and external parties. However, challenges include limited technological infrastructure in schools and a lack of teacher training. Therefore, strategic steps are needed to optimize the role of technology in GC services at the elementary school level. This study provides insights into the importance of technology in improving the quality of GC services in the digital age.